Determinan Emisi CO2 pada Negara Anggota ASEAN Tahun 2015-2022 - Farhan Rafif Santana; Nugroho Sumarjiyanto Benedictus Maria (Diponegoro Journal of Economics, 2024)
This study aims to test the Environmental Kuznets Curve (EKC) hypothesis in ASEAN member countries from 2015 to 2022 and to analyze the effect of per capita GDP, population size, energy transition, foreign investment, and trade openness on carbon emissions in ASEAN member countries from 2015 to 2022. This research uses a quantitative approach with data sourced from the International Energy Agency and the World Bank. The analytical method applied is multiple linear regression using panel data from 10 ASEAN countries for the period 2015-2022. The results show that the Environmental Kuznets Curve (EKC) hypothesis is confirmed in ASEAN member countries for the period 2015-2022, with a turning point for the relationship between per capita GDP and CO2 emissions in the ASEAN region at 17.11 trillion dollars. Singapore and Brunei Darussalam are the two countries among 11 in the ASEAN region that have passed the scale and structural effect phase on the Environmental Kuznets Curve, while others remain on the left side of the EKC. Per capita GDP can significantly increase or reduce carbon emissions in the ASEAN region depending on whether the member country has reached the EKC turning point phase. Population size, foreign investment, and trade openness significantly increase carbon emissions in the ASEAN region. The energy transition can reduce carbon emissions in the ASEAN region, though not significantly.